Pengaruh Human Relationship dan Beban Kerja terhadap Kinerja Pegawai - Eka Farida; Neneng Rika Jazilatul Kholidah (Jurnal Ecogen, 2021)
Organization will produce good employee performance if it is able to pay attention to the factors of providing workload. To reduce the workload that is too high there needs to be a human relationship that can provide lightening in completing workloads in the organization. The purpose of this study is to examine the performance of BKPSDM employees influenced by human relationships and workloads. This research is ex-post facto by using primary data. Population and samples in this study using non probability sampling techniques with a total of 52 respondents. The analysis used in this study is multiple regression analysis. The results showed that the performance of BKPSDM employees was influenced by human relationships and workloads.Keywords : employee performance, human relationship, workload